Analysis of Fiscal Dependence of Local Governments in Papua Province in the Special Autonomic Era - Muhammad Dimyati Sudja; Kumba Digdowiseiso; Dewi Susilawati; Indah Dian (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Regional autonomy in Indonesia has an impact on regional politics and finance. Regions that were initially limited by financial receipts from the center now have the opportunity to meet their needs independently. This is known as fiscal decentralization which has been implemented in various regions, including in Papua. The method used in this research is literature study. This method is used in order to answer the research objective, namely to explore the implementation of fiscal decentralization in Indonesia, Papua. The results obtained, it is known that although fiscal decentralization has been carried out in the long term, there are still regions that are unable to carry it out. As a result, these regions are still dependent on funding from the center. In Papua, for example, this is due to the large amount of regional expenditure compared to regional income. Programs made by the regions require a lot of costs compared to the income they have, so the central government needs to provide financial support. Another reason is that BUMD has not been able to provide a maximum role in generating PAD. This is because BUMD is not able to compete with its competitors. As a result, the PAD generated is not optimal and some even cause losses. To overcome this, one of the steps that can be taken is to maximize the role of Regional Owned Enterprises so that they are able to increase regional income and release regional dependence from the center. This is because BUMD is not able to compete with its competitors. As a result, the PAD generated is not optimal and some even cause losses. To overcome this, one of the steps that can be taken is to maximize the role of Regional Owned Enterprises so that they are able to increase regional income and release regional dependence from the center. This is because BUMD is not able to compete with its competitors. As a result, the PAD generated is not optimal and some even cause losses. To overcome this, one of the steps that can be taken is to maximize the role of Regional Owned Enterprises so that they are able to increase regional income and release regional dependence from the center.